WILLIAMSON MODEL: AN APPLICATION OF INSTITUTIONAL TRANSFORMATION IN THE INDONESIAN DGT - Jaya, Wihana Kirana; Rahajeng, Anggi; Bastian, Indra (Journal of Indonesian Economy and Business, 2014)
A reform of tax administration in Indonesia has been carried out in several stages from 1983to 2009. However, the changes are limited to the tax system of the DGT, it being the tax governingbody in Indonesia, which has still has not managed to meet the tax revenue target (reflectedthrough a tax ratio). A lack of authority caused the DGT (DGT) to face some difficulties inreaching the target and demonstrating the expected performance. The goal of this paper is tostress the needs of institutional transformation in DGT. By using the Williamson Model, thisstudy focuses on evaluating the DGT institutionally and creating an alternative institutionaltransformation of the DGT. The international and domestic results of ascertaining bestpractices conclude that the DGT needs to change gradually, not with a âbig bangâ, and byproviding the more flexible authority by remaining in the structure of Traditional Departmentor Single Directorate in the Ministry of Finance (SDMOF) which would lead to an organizationstructure which is semi-autonomous or a Unified Semi-autonomous Body (USB) that covers allthe systems of taxation such as service, assurance, law enforcement and supporting roles.Keywords: tax governing body, Indonesian DGT (DGT), institutional transformation,Â williamson model